WORKSTATION BEKERJA DARI RUMAH/HYBRID: (KOLABORASI DENGAN PT ROVEGA INDONESIA) (LPPM Institut Desain dan Bisnis Bali, 2024)
The local retail market complained about the sluggish furniture business during and after the pandemic. However, overseas furniture retailers such as Wayfair and Ashley Furniture actually shot up sales because they quickly responded to the market need to work from home, through innovative furniture designs and answering consumer demand. This research was conducted with an iterative convergent divergent method through the stages of the design process, discussions with furniture experts (both industry players and academics), and reviews through a 1: 1 prototype. Through collaboration with Rovega Furniture, UPH's research team aims to: 1) produce 20 alternative designs and 3 final designs that can be marketed for work from home needs; 2) Provide opportunities for student research teams to gain professional experience with reputable local furniture industry stakeholders. This research is expected to contribute to reviving the sluggish local market.